Analysis of Teacher Challenges and Solutions in Implementing Learning Strategies - Harahap, Dian; Silalahi, Diana; Hutagalung, Enjelita; Purba, Mayesa; Tansliova, Lili (CV. Rayyan Dwi Bharata, 2024)
Strategy is an effort to achieve success and success in achieving learning goals. The purpose of this research is to find out what the challenges and solutions are for teachers in implementing Indonesian language learning strategies. This research was conducted using a qualitative literature study approach, which involved collecting various reference analyzes related to the research topic. The results of this research are that teachers must implement learning strategies in the classroom. Even though teachers often face challenges in implementing learning strategies in the classroom, teachers must be able to overcome them and not make these problems become stumbling blocks in educating the nation's children.